Behavior regulation skills are associated with adaptive functioning in children and adolescents with prenatal alcohol exposure. Issue 4 (2nd October 2022) - Gardiner, Emily; Hutchison, Sarah M.; McLachlan, Kaitlyn; Rasmussen, Carmen; Pei, Jacqueline; Mâsse, Louise C.; Oberlander, Tim F.; Reynolds, James N.
Abstract: Children with prenatal alcohol exposure (PAE) experience a range of adverse outcomes that impact multiple domains of functioning, including cognitive, physical, mental health, behavioral, social-emotional, communication, and learning. To inform tailored clinical intervention, the current study examined the relation between caregiver-reported cognitive skills (executive function; EF) and adaptive functioning. The study conducted a secondary analyses of data provided by caregivers of 87 children and adolescents (aged 5–18 years, M  = 11.7; 52% male) with confirmed PAE, including a subset ( n  = 70) with Fetal Alcohol Spectrum Disorder (FASD), who reported on their child's EF (Behavior Rating Inventory of Executive Function) and adaptive function (Adaptive Behavior Assessment System, 2nd Edition) skills. Findings from the current study showed that caregivers reported significantly poorer EF and adaptive functioning skills for children with PAE as compared to normative samples. Poorer behavior regulation skills were associated with all aspects of adaptive functioning (i.e., practical, conceptual, and social skills). Specifically, shifting skills emerged as the best predictor of adaptive functioning among children with PAE. These results highlight the possibility that targeting particular EF domains among individuals with PAE may benefit behavior regulation, which may also extend to adaptive skills. This highlights the need to develop EF interventions for children and adolescents who have been prenatally exposed to alcohol.